2008
DOI: 10.1002/elan.200704071
|View full text |Cite
|
Sign up to set email alerts
|

Lignosulfonate‐Modified Electrode for Electrocatalytic Reduction of Acidic Nitrite

Abstract: Sodium lignosulfonate (LS) undergoes oxidative electropolymerization on a glassy carbon (GC) electrode from sulfuric acid solution to form a chemically modified electrode exhibiting anionic character and redox activity. Cyclic voltammetry reveals the existence of two redox systems at E8' values of þ 0.29 and þ 0.53 V, respectively. Peak currents are proportional to the scan rate as expected for surface confined systems. The GC j poly-LS electrode shows electrocatalytic activity toward the reduction of acidic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“…As shown in Fig.2 (A), CVs of the lignin modified electrode show reversible redox couples (quinone/hydroquinone) in the potential between 0.35 V to 0.55 V which in agreement with literature results [14][15] . Both anodic and cathodic peak potentials are also independent of the scan rates.…”
Section: Electrochemical Characterization Of Lg/gcesupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig.2 (A), CVs of the lignin modified electrode show reversible redox couples (quinone/hydroquinone) in the potential between 0.35 V to 0.55 V which in agreement with literature results [14][15] . Both anodic and cathodic peak potentials are also independent of the scan rates.…”
Section: Electrochemical Characterization Of Lg/gcesupporting
confidence: 90%
“…Papers are dedicated to the lignin oxidation on different electrodes for the sake of the development of a voltammetric lignin analysis method such as adsorption on polycrystalline gold electrodes 13 , Lignosulfonate modified glassy carbon electrode 14 , polypyrrole/lignin composite [15][16] , chloroaniline/lignin 17 have been discussed. This paper reports the successful preparation of composites modified electrode on glassy carbon electrode surface (LG/GCE, AHNSA/GCE, POPDA/ GCE, and its composite (LG-co-AHNSA and LGco-OPDA) by repetitive CV scans, to improve the electrochemical behavior of the prepared modified electrode by Cyclic voltammetry, Electrochemical Quartz Crystal Microbalance (EQCM) techniques and characterize with Fourier transform infrared spectroscopy (FTIR).…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…The same authors also studied the electrochemistry of lignosulfonate on glassy carbon (GC) and reported that it did not undergo electropolymerization on this electrode. Contrary to the latter observation, Milczarek [23] electropolymerized lignosulfonate from an acidic electrolyte on to a GC electrode and observed high redox activity of the formed coating, which could be practically applied to the electrocatalytic reduction of acidic nitrite. The discrepancy in the polymerization ability may come from the different sources of lignosulfonates used in the two studies.…”
Section: Introductionmentioning
confidence: 61%
“…262 Other than the lignin-polypyrrole conjugated electrode, series of lignin-modifi ed electrodes were reported with showing high electrochemical activity and material stability. [269][270][271][272] As a none electrochemical applications of ligninpolyaniline composite, He et al recently reported that enzymatic hydrolysis lignin/polyaniline composite, which shows high-silverion adoption property on the composite surface. …”
Section: Polyaniline and Polypyrrolementioning
confidence: 99%